TRANSISI PEMUDA DALAM MASYARAKAT RISIKO: ANTARA ASPIRASI, HAMBATAN DAN KETIDAKPASTIAN - Oki Rahadianto Sutopo (Universitas Paramadina, 2014)
This article explains about the aspirations, obstacles and uncertainties of youth transition from school to work using youth transition and risk society perspective. It is more difficult for young peopleto handle the transition in the conditions of late modernity era. They have to deal withuncertainty and risk without certain direction of their future. As one of the consequences in the risk society, young people are more individualize to create their own biographical trajectories.They have to make their own plans both related to education and work. Individualization is becoming the new social structure, where people seek biographical solutions to systematic contradictions embedded in late modernity. However, youth transition from school to work still has to deal with many layers of structural obstacles. As a solution, the state role needs to be reinforced to protect young people from risk in the future.